2020
DOI: 10.1007/s00068-020-01534-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 pandemic on general surgical emergencies: are some emergencies really urgent? Level 1 trauma center experience

Abstract: Purpose The aim of this paper is to investigate the effect of COVID-19 pandemic on general surgical emergencies as well as analyzing the effectiveness of measures taken in reducing the incidence of COVID-19 in patients and healthcare professionals. Methods Patients who underwent emergency surgery between the pandemic period of March 14th to May 15th 2020 and within the same period from the previous year were reviewed retrospectively. COVID-19 incidence in patients and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 21 publications
6
47
3
3
Order By: Relevance
“…26 studies described a change in case number of appendicitis and/or appendectomies between comparable time periods before and during the COVID-19 pandemic in adults [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. Studies were conducted in 15 countries (as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…26 studies described a change in case number of appendicitis and/or appendectomies between comparable time periods before and during the COVID-19 pandemic in adults [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. Studies were conducted in 15 countries (as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although postponing elective hernia operations during the pandemic has raised concerns that the number of EAAWHS may increase due to incarceration or strangulation, recent studies have reported a decrease in the number of patients [ 21 , 22 ]. In our study, 41 patients were operated emergently during the pandemic, while 24 patients were operated during the control period.…”
Section: Discussionmentioning
confidence: 99%
“…In short-term studies with a low number of EAAWHS cases, it was reported that EAAWHS was decreased during the pandemic period compared to the control period. [ 21 , 22 ]. Oscar Cano-Valderemma et al reported a decrease in the number of general surgery emergency groups but an increased number of incarcerated hernia cases [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery delays are associated with poorer prognosis, and the increased morbidity and mortality cannot be ignored. 1 3 …”
Section: Introductionmentioning
confidence: 99%